Development and testing of a transcatheter heart valve with reduced calcification potential - Weich, Hellmuth; Botes, Lezelle; Doubell, Anton; Jordaan, Johan; Lewies, Angelique; Marimuthu, Prennie; van den Heever, Johannes; Smit, Francis (Frontiers in Cardiovascular Medicine, 2023)
Patients from developing countries who require heart valve surgery are younger and have less access to open heart surgery than in developed countries. Transcatheter heart valves [THV] may be an alternative but are currently unsuitable in young patients because of inadequate durability. We set out to develop and test a THV utilizing two new types of decellularized bovine pericardial leaflets in the ovine model.The two decellularized tissues [one with very low dose [0.05%] monomeric glutaraldehyde fixation and detoxification (DF) and the other without glutaraldehyde (DE)] were compared to an industry standard [Glycar ® -fixed with standard dose (0.625%) glutaraldehyde]. THVs were manufactured with the three tissue types and implanted in the pulmonary position of 9 juvenile sheep for 180 days. Baseline and post explant evaluation were performed on hemodynamic performance of the valves, dynamic strength testing, structure, biological interaction and calcification.One animal developed heart failure due to incompetence of its Glycar ®valve and was euthanized at 158 days. The gradients over the Glycar ® valves were higher at explant than implant but the DE and DF valves maintained normal hemodynamic performance throughout. The DF and DE tissues performed well on mechanical testing of explanted leaflets. Glycar ® tissue developed thick pannus and calcification. Compared to Glycar ®, the DF tissue exhibited reduced pannus overgrowth and calcification and the DE tissue exhibited no pannus formation, calcification. All tissues endothelialized adequately. There was a striking absence of host ingrowth in the DE tissue leaflets, yet these leaflets maintained integrity and mechanical function.In the juvenile sheep THV model, Glycar ® tissue developed significant pannus, calcification and hemodynamic deterioration. Using very low dose monomeric GA to fix decellularized bovine pericardium yielded less pannus formation, less calcification and better hemodynamic function. We postulate that the limited pannus formation in the DF group is as a result of GA. Bovine pericardium decellularized with our proprietary method resulted in tissue that was inert which is a unique finding. These results justify further development and evaluation of the two decellularized tissue types in THVs aimed at use in younger patients.